On Resistance and Inductance of Solid Conductors - Oldřich Coufal (Journal of Engineering)
The concepts of resistance and inductance are strewn with misunderstanding and errors that result from inaccurate terminology, mistakes in their definitions, and from the fact that they are quantities that characterize elements of ideal electrical circuits as well as real solid conductors. This is shown unfavourably not only in the respective field of the theory of electrical engineering, but also in the calculation of resistance and inductance. In this paper, a brief theoretical analysis of the state of the art is given, and its results are applied in the calculation of the current density, resistance, and inductance of two coaxial solid tubular conductors.